Videoformes : Festival de la Création Vidéo. - Videoformes Clermont-Ferrand 1991 (Clermont-Ferrand : Videoformes, 1991)
Vom Bruch, Klaus ; Corsino, Nicole ; Corsino, Norbert ; Esthetu, Théo ; Ronce, Philippe ; Kuzminska, Julie ; Machine, Dépanne ; Barret, Clémence ; Melgar, Fernand ; Goel, Stéphane ; Wahorn, Andras ; Martinis, Dalibor ; Groscolas, Anne-Marie ; Barbieri, Renato ; Poirson, Jean-Claude ; Alvarez, Julian ; Lefdup, Jérôme ; etc.
Videoformes : Festival de la Création Vidéo, Clermont-Ferrand, 3 au 20 Avril 1991
boek